HT-SuMD: making molecular dynamics simulations suitable for fragment-based screening. A comparative study with NMR. (1st January 2021) - Ferrari, Francesca; Bissaro, Maicol; Fabbian, Simone; De Almeida Roger, Jessica; Mammi, Stefano; Moro, Stefano; Bellanda, Massimo; Sturlese, Mattia
Abstract: Fragment-based lead discovery (FBLD) is one of the most efficient methods to develop new drugs. We present here a new computational protocol called High-Throughput Supervised Molecular Dynamics (HT-SuMD), which makes it possible to automatically screen up to thousands of fragments, representing therefore a new valuable resource to prioritise fragments in FBLD campaigns. The protocol was applied to Bcl-XL, an oncological protein target involved in the regulation of apoptosis through protein–protein interactions. Initially, HT-SuMD performances were validated against a robust NMR-based screening, using the same set of 100 fragments. These independent results showed a remarkable agreement between the two methods. Then, a virtual screening on a larger library of additional 300 fragments was carried out and the best hits were validated by NMR. Remarkably, all the in silico selected fragments were confirmed as Bcl-XL binders. This represents, to date, the largest computational fragments screening entirely based on MD.